Congenital and acquired tooth loss-a causative factors among children - S, SNEHA SREE.; P, DR.JESSY; VADIVEL, DR.JAYANTH KUMAR (The journal of contemporary issues in business and government, 2021)
Tooth loss can rob people of much more than the ability to chew and properly digest food. It has serious social, psychological and emotional consequences, impacting quality of life, self image and self esteem.The aim of this study is to investigate early loss of permanent teeth and its causative factors below 18 yrs old children. A retrospective study was conducted using the patient records of children visiting Saveetha dental college.The children between 6-18 years with early permanent tooth loss were selected for this study.Data including age,tooth loss and its reason was collected.The data collected were entered into SPSS version 20.0 and subjected to statistical analysis.Level of significance was set at 5% (p<0.05). Descriptive statistics and chi square test were applied .The results showed overall prevalence of permanent tooth loss,15.09%, dental caries was the main causative factor (31.85%) in 16-18 year old children showing statistical significant difference (p<0.05) and about 56.8% male predominance.It can be concluded that dental caries remains a real public health problem in developing countries. Decision makers need to focus on strategies on prevention of dental caries.